Molecular sieve SSZ-122, its synthesis and use

By preparing BOG skeleton aluminosilicate molecular sieve containing 1-adamantyl-3-propylimidazolium cations, the low efficiency and poor selectivity of BOG skeleton molecular sieve in the conversion and adsorption process of organic compounds in the prior art are solved. Problem, achieving efficient catalytic and adsorption effects, suitable for commercial applications.

CN116133988BActive Publication Date: 2024-12-17CHEVRON USA INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180061475.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-21
Filing Date
2021-05-19
Publication Date
2024-12-17
Estimated Expiration
2041-05-19

AI Technical Summary

Technical Problem

The existing BOG skeleton aluminosilicate molecular sieve has problems of low efficiency and poor selectivity during the conversion and adsorption of organic compounds, and it is difficult to use stably in commercial applications.

Method used

By preparing a reaction mixture containing 1-adamantyl-3-propylimidazolium cations, combined with FAU backbone zeolite, alkali or alkaline earth metal, hydroxide ion source and water, a BOG with a SiO2/Al2O3 molar ratio of at least 10 Skeleton-type aluminosilicate molecular sieve and contains organic cations in its pores in the synthetic form as it is used as catalysts for organic compound conversion and adsorption processes.

Benefits of technology

It achieves efficient catalytic and adsorption effects during organic compound conversion and adsorption, improves the selectivity and stability of the catalyst, and is suitable for various organic compound conversion processes in commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116133988B_ABST
    Figure CN116133988B_ABST
Patent Text Reader

Abstract

A BOG framework-type aluminosilicate molecular sieve material is provided, named SSZ-122. SSZ-122 can be synthesized using 1-adamantyl-3-propylimidazolium cation as a structure directing agent. SSZ-122 can be used in organic compound conversion and / or adsorption processes.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of U.S. Provisional Application No. 63 / 054,330, filed on July 21, 2020. Technical Field

[0003] The present disclosure relates to a novel synthetic crystalline molecular sieve of BOG framework type named SSZ-122, its synthesis and its use in organic compound conversion and adsorption processes. Background Art

[0004] Molecular sieves are a class of commercially important materials that have a unique crystal structure with a defined pore structure, as shown by a unique X-ray diffraction (XRD) pattern, and a specific chemical composition. The crystal structure defines the characteristic cavities and pores of a particular type of molecular sieve.

[0005] Molecular sieves are classified by the International Zeolite Association Structure Commission according to the rules of the IUPAC Zeolite Nomenclature Committee. According to this classification, framework zeolites and other crystalline microporous molecular sieves with established unique structures are assigned a three-letter code and described in, for example, Ch. Baerlocher, LB McCusker and DH Olson's "Atlas of Zeolite Framework Types" (Elsevier, Sixth Revised Edition, 2007).

[0006] The natural mineral boggsite is a molecular sieve material with a unique 10-ring and 12-ring three-dimensional channel system. The International Zeolite Association Structure Committee has designated the framework structure of boggsite as the three-letter code BOG.

[0007] According to the present disclosure, a BOG framework-type aluminosilicate molecular sieve, named SSZ-122, has now been synthesized using 1-adamantyl-3-propylimidazolium cation as a structure directing agent. Summary of the invention

[0008] In a first aspect, a BOG framework-type aluminosilicate molecular sieve is provided, wherein the aluminosilicate molecular sieve has a SiO2 / Al2O3 molar ratio of at least 10.

[0009] In a second aspect, there is provided a BOG framework-type aluminosilicate molecular sieve comprising, in its as-synthesized form, 1-adamantyl-3-propylimidazolium cations in its pores.

[0010] In a third aspect, a method for synthesizing a BOG framework-type aluminosilicate molecular sieve is provided, the method comprising (1) preparing a reaction mixture comprising: (a) a FAU framework-type zeolite; (b) an alkali metal or alkaline earth metal (M) source; (c) a structure directing agent comprising a 1-adamantyl-3-propylimidazolium cation (Q); (d) a hydroxide ion source; and (e) water; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the aluminosilicate molecular sieve.

[0011] In a fourth aspect, a method for converting a feedstock comprising an organic compound into a conversion product is provided, comprising contacting the feedstock with a catalyst comprising a BOG framework-type aluminosilicate molecular sieve under organic compound conversion conditions, wherein the aluminosilicate molecular sieve has a SiO2 / Al2O3 molar ratio of at least 10. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is a scanning electron micrograph (SEM) image of the as-synthesized SSZ-122 of Example 1.

[0013] Figure 2 Powder X-ray diffraction (XRD) patterns of the as-synthesized SSZ-122 of Example 1 (bottom graph) and the calcined SSZ-122 of Example 6 (top graph) are compared. DETAILED DESCRIPTION

[0014] definition

[0015] The term "zeolite" herein refers to a molecular sieve having a framework composed of TO4 tetrahedra, with the T atoms being silicon and aluminum atoms.

[0016] The term "framework type" has the meaning described in "Atlas of Zeolite Framework Types" by Ch. Baerlocher, LB McCusker and DH Olson (Elsevier, 6th revised edition, 2007).

[0017] The term "as-synthesized" refers to the molecular sieve in its form after crystallization and before removal of the structure directing agent.

[0018] The term "anhydrous" refers to a molecular sieve that is substantially free of physically adsorbed water and chemically adsorbed water.

[0019] The term "SiO2 / Al2O3 molar ratio" may be abbreviated as "SAR".

[0020] Synthesis of molecular sieves

[0021] Molecular sieve SSZ-122 can be synthesized by the following steps: (1) preparing a reaction mixture comprising: (a) FAU framework-type zeolite; (b) an alkali metal or alkaline earth metal (M) source; (c) a structure directing agent comprising a 1-adamantyl-3-propylimidazolium cation (Q); (d) a hydroxide ion source; and (e) water; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the aluminosilicate molecular sieve.

[0022] The reaction mixture may have a composition within the range listed in Table 1, in terms of molar ratio:

[0023] Table 1

[0024] Reactants The most extensive Typical <![CDATA[SiO2 / Al2O3]]> ≥10 20 to 60 <![CDATA[M / SiO2]]> 0.05 to 0.50 0.10 to 0.40 <![CDATA[Q / SiO2]]> 0.01 to 0.30 0.05 to 0.20 <![CDATA[OH / SiO2]]> 0.20 to 0.60 0.30 to 0.50 <![CDATA[H2O / SiO2]]> 15 to 60 20 to 40

[0025] wherein M is an alkali metal or an alkaline earth metal, and Q comprises a 1-adamantyl-3-propylimidazolium cation.

[0026] The FAU framework zeolite can be an ammonium zeolite or a hydrogen zeolite (e.g., NH4 zeolite Y, H zeolite Y). The example of the FAU framework zeolite includes zeolite Y (e.g., CBV712, CBV720, CBV760, CBV780, HSZ-HUA385, and HSZ-HUA390). Preferably, the FAU framework zeolite is zeolite Y. Zeolite Y can have a SiO2 / Al2O3 molar ratio of about 12 to about 500. The FAU framework zeolite can include two or more zeolites. Typically, the two or more zeolites are zeolites Y with different silica to alumina molar ratios. The FAU framework zeolite can also be the only silicon and aluminum source to form SSZ-122.

[0027] Alkali metals or alkaline earth metals (M) are usually introduced into the reaction mixture together with a source of hydroxide ions. Examples of such metals include sodium and / or potassium, as well as lithium, rubidium, cesium, magnesium and calcium. As used herein, the phrase "alkali metal or alkaline earth metal" does not mean that alkali metals and alkaline earth metals are used interchangeably, but rather means that one or more alkali metals can be used alone or in combination with one or more alkaline earth metals and one or more alkaline earth metals can be used alone or in combination with one or more alkali metals.

[0028] The structure directing agent used to prepare SSZ-122 comprises a 1-adamantyl-3-propylimidazolium cation (Q) represented by the following structure (1):

[0029]

[0030] Suitable sources of Q are hydroxides, chlorides, bromides and / or other salts of quaternary ammonium compounds.

[0031] The reaction mixture may contain seeds of crystallization material, such as SSZ-122 from a previous synthesis, desirably in an amount of 0.01 to 10,000 ppm (e.g., 100 to 5000 ppm) based on the weight of the reaction mixture. Seeding may be beneficial to increase selectivity to SSZ-122 and / or shorten the crystallization process.

[0032] It should be noted that the reaction mixture components may be provided by more than one source. In addition, two or more reaction components may be provided by one source. The reaction mixture may be prepared batchwise or continuously.

[0033] Crystallization and post-synthesis processing

[0034] Crystallization of the molecular sieve from the above reaction mixture can be carried out in a suitable reaction vessel, such as a polypropylene tank or a polytetrafluoroethylene liner or a stainless steel autoclave, under static, tumbling or stirring conditions, at a temperature of 120° C. to 200° C. (e.g., 140° C. to 180° C.) for a time sufficient to allow crystallization to occur at the temperature used (e.g., 1 day to 21 days, or 3 days to 16 days). Crystallization is usually carried out in an autoclave to subject the reaction mixture to autogenous pressure.

[0035] Once the desired molecular sieve crystals are formed, the solid product is separated from the reaction mixture by standard separation techniques such as filtration or centrifugation. The recovered crystals are washed with water and then dried for a few seconds to a few minutes (e.g., flash drying for 5 seconds to 10 minutes) or a few hours (e.g., oven drying at 75° C. to 150° C. for 4 to 24 hours) to obtain as-synthesized SSZ-122 crystals having at least a portion of the organic cations in their pores. The drying step can be carried out at atmospheric pressure or under vacuum.

[0036] The synthesized molecular sieve may be subjected to heat treatment, ozone treatment or other treatment to remove some or all of the structure directing agents used in its synthesis. The removal of the structure directing agent may be carried out by heat treatment (i.e., calcination), wherein the synthesized molecular sieve is heated in air or an inert gas at a temperature sufficient to remove some or all of the structure directing agents. Although less than atmospheric pressure may be used for heat treatment, atmospheric pressure is desired for convenience reasons. The heat treatment may be carried out at a temperature of at least 370°C for at least one minute and generally not longer than 20 hours (e.g., 1 to 12 hours). The heat treatment may be carried out at a temperature of up to 925°C. For example, the heat treatment may be carried out in air at a temperature of 400°C to 600°C for about 1 to 8 hours.

[0037] Any extra-framework metal cations in the molecular sieve may be replaced with hydrogen, ammonium, or any desired metal cation according to techniques well known in the art (eg, by ion exchange).

[0038] Characterization of Molecular Sieve

[0039] Molecular sieve SSZ-122, in its as-synthesized and anhydrous form, may have a chemical composition within the range listed in Table 2, in terms of molar ratios:

[0040] Table 2

[0041] The most extensive Typical <![CDATA[SiO2 / Al2O3]]> ≥10 20 to 60 <![CDATA[Q / SiO2]]> >0 to 0.1 >0 to 0.1 <![CDATA[M / SiO2]]> >0 to 0.1 >0 to 0.1

[0042] wherein Q comprises a 1-adamantyl-3-propylimidazolium cation, and M is an alkali metal or an alkaline earth metal.

[0043] Molecular sieve SSZ-122, in its calcined form, may have a chemical composition comprising the following molar relationship:

[0044] Al2O3:(n)SiO2

[0045] wherein n is at least 10 (eg, 10 to 100, 10 to 60, 20 to 100, or 20 to 60).

[0046] The framework structure of SSZ-122 may be free or substantially free of T atoms (tetrahedral atoms) other than silicon and aluminum. As used herein, the term "substantially free" means that the molecular sieve contains less than 0.1% or 0.01% of a specified framework impurity.

[0047] The powder XRD pattern representing the BOG framework type molecular sieve can be referred to in "Collection of Simulated XRD Powder Patterns for Zeolites" by MMJ Treacy and JB Higgins (Elsevier, fifth revised edition, 2007).

[0048] The powder XRD patterns presented herein were collected by standard techniques. Changes in the molar ratio of the framework material of a particular sample may cause minor changes in the diffraction pattern due to changes in the lattice constant. In addition, sufficiently small crystals can affect the shape and intensity of the peaks, resulting in an apparent broadening of the peaks. Changes in the organic compounds used in the preparation may also cause minor changes in the diffraction pattern. Calcination can also cause slight changes in the XRD pattern. Despite these minor perturbations, the basic lattice structure remains unchanged.

[0049] Industrial Applicability

[0050] Molecular sieve SSZ-122 (in which some or all of the structure directing agent is removed) can be used as an adsorbent or catalyst to catalyze various organic compound conversion processes, including many processes of existing commercial / industrial importance. Examples of chemical conversion processes that are effectively catalyzed by SSZ-122 itself or in combination with one or more other catalytically active materials (including other crystalline catalysts) include those that require a catalyst with acid activity. Examples of organic conversion processes that can be catalyzed by SSZ-122 can include cracking, hydrocracking, disproportionation, alkylation, oligomerization, and isomerization.

[0051] As is the case with many catalysts, it may be necessary to combine SSZ-122 with another material that is resistant to the temperatures and other conditions used in organic conversion processes. Such materials include active and inactive materials and synthetic or naturally occurring zeolites and inorganic materials such as clays, metal oxides such as silica and / or alumina. The latter may be naturally occurring or in the form of colloidal precipitates or gels, including mixtures of silica and metal oxides. Materials used in combination with active SSZ-122 (i.e., combined with it or present in the synthesis of new materials) tend to change the conversion rate and / or selectivity of the catalyst in certain organic conversion processes. Inactive materials are suitable for use as diluents to control the amount of conversion in a given process, so that the product can be obtained in an economical and orderly manner without using other methods to control the reaction rate. These materials can be incorporated into naturally occurring clays (e.g., bentonite and kaolin) to increase the crush strength of the catalyst under commercial operating conditions. These materials (i.e., clays, oxides, etc.) are used as binders for catalysts. It is desirable to provide a catalyst with good crush strength because it is desirable to prevent the catalyst from decomposing into a powdery material in commercial applications. These clay and / or oxide binders are generally used only to increase the crush strength of the catalyst.

[0052] Natural clays that can be compounded with SSZ-122 include montmorillonite and kaolin families, which include sub-bentonites, and kaolins commonly known as Dixie, McNamee, Georgia and Florida clays, or other clays whose main mineral components are halloysite, kaolinite, dickite, perlite or silica-rich kaolinite. Such clays can be used in the original state of initial mining or in the state of initial calcination, acid treatment or chemical modification. Binders that can be used for compounding with SSZ-122 also include inorganic oxides such as silicon dioxide, zirconium oxide, titanium dioxide, magnesium oxide, beryllium oxide, aluminum oxide and mixtures thereof.

[0053] In addition to the materials described above, SSZ-122 can be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, and ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia.

[0054] The relative proportions of SSZ-122 and the inorganic oxide matrix can vary widely, with the SSZ-122 content ranging from 1 to 90 weight percent (eg, 2 to 80 weight percent) of the composite.

[0055] Example

[0056] The following illustrative examples are intended to be non-limiting.

[0057] Example 1

[0058] 2.18g deionized water, 0.20g 45% KOH solution, 1.55g 13.62% 1-adamantyl-3-propylimidazolium hydroxide solution and 0.50g Zeolyst CBV720 Y-zeolite powder (SAR=30) were mixed together in a polytetrafluoroethylene liner. The resulting gel was stirred until it became uniform. The liner was then covered with a lid and placed in a Parr Steel autoclave reactor. The autoclave was then placed in an oven heated at 150°C for 10 days while tumbling at 43rpm. The solid product was recovered from the cooled reactor by centrifugation, washed with deionized water and dried at 95°C.

[0059] The obtained products were analyzed by SEM and powder XRD. Figure 1 The powder XRD pattern of the as-synthesized material is shown in Figure 2 and is consistent with a material having a BOG framework-type structure.

[0060] The product had a SiO2 / Al2O3 molar ratio of 24.2, as determined by elemental analysis by inductively coupled plasma-atomic emission spectroscopy (ICP-AES).

[0061] Example 2

[0062] 4.35 g of deionized water, 0.40 g of 45% KOH solution, 3.01 g of 13.62% 1-adamantyl-3-propylimidazolium hydroxide solution and 1.00 g of Zeolyst CBV720 Y-zeolite powder (SAR=30) were mixed together in a polytetrafluoroethylene liner. The gel was stirred until it became uniform. The liner was then covered with a lid and placed in a Parr Steel autoclave reactor. The autoclave was then placed in an oven heated at 160° C. under static conditions for 14 days. The solid product was recovered from the cooled reactor by centrifugation, washed with deionized water and dried at 95° C.

[0063] The obtained product was identified as a pure aluminosilicate molecular sieve with a BOG framework structure by SEM and powder XRD.

[0064] The product had a SiO2 / Al2O3 molar ratio of 25.5 as determined by ICP-AES elemental analysis.

[0065] Example 3

[0066] 1.31 g of deionized water, 0.12 g of 50% NaOH solution, 0.93 g of 13.62% 1-adamantyl-3-propylimidazolium hydroxide solution and 0.30 g of Zeolyst CBV760 Y-zeolite powder (SAR=60) were mixed together in a polytetrafluoroethylene liner. The resulting gel was stirred until it became uniform. The liner was then covered with a lid and placed in a Parr Steel autoclave reactor. The autoclave was then placed in an oven heated at 150° C. under static conditions for 10 days. The solid product was recovered from the cooled reactor by centrifugation, washed with deionized water and dried at 95° C.

[0067] The obtained product was identified as a pure aluminosilicate molecular sieve with a BOG framework structure by powder XRD and SEM.

[0068] The product had a SAR of 48.8 as determined by ICP-AES elemental analysis.

[0069] Example 4

[0070] 0.50 g of deionized water, 0.12 g of 45% KOH solution, 1.86 g of 13.62% 1-adamantyl-3-propylimidazolium hydroxide solution and 0.30 g of Zeolyst CBV720 Y-zeolite powder (SAR=30) were mixed together in a polytetrafluoroethylene liner. The gel was stirred until it became uniform. The liner was then covered with a lid and placed in a Parr Steel autoclave reactor. The autoclave was then placed in an oven heated at 150° C. under static conditions for 16 days. The solid product was recovered from the cooled reactor by centrifugation, washed with deionized water and dried at 95° C.

[0071] The obtained product was identified as a pure aluminosilicate molecular sieve with a BOG framework structure by powder XRD and SEM.

[0072] The product had a SiO2 / Al2O3 molar ratio of 24.7 as determined by ICP-AES elemental analysis.

[0073] Example 5

[0074] 1.51 g of deionized water, 0.20 g of 45% KOH solution, 2.33 g of 13.62% 1-adamantyl-3-propylimidazolium hydroxide solution, 0.50 g of Zeolyst CBV712 Y-zeolite powder (SAR=12) and 0.08 g of as-synthesized SSZ-122 seeds from Example 1 were mixed together in a polytetrafluoroethylene liner. The gel was stirred until it became homogeneous. The liner was then covered with a lid and placed in a Parr Steel autoclave reactor. The autoclave was then placed in an oven heated at 150° C. for 7 days while tumbling at 43 rpm. The solid product was recovered from the cooled reactor by centrifugation, washed with deionized water and dried at 95° C.

[0075] The obtained product was identified as a pure aluminosilicate molecular sieve with a BOG framework structure by powder XRD and SEM.

[0076] The product had a SiO2 / Al2O3 molar ratio of 12.7 as determined by ICP-AES elemental analysis.

[0077] Example 6

[0078] The as-synthesized molecular sieve product from Example 1 was calcined in a muffle furnace under air flow heated to 540°C at a rate of 1°C / min and maintained at 540°C for 5 hours, cooled, and then analyzed by powder XRD. The powder XRD of the calcined material is as follows: Figure 2 This is shown and demonstrates that the material remains stable after calcination to remove the structure directing agent.

[0079] Example 7

[0080] The calcined material from Example 5 was treated with 10 mL (per g of molecular sieve) of 1 N ammonium nitrate solution at 95°C for 2 hours. The solution was cooled, decanted and the same process was repeated. After drying, the ammonium product was subjected to micropore volume analysis by the BET method using N2 as the adsorbent. The molecular sieve exhibited a micropore volume of 0.21 cm 3 / g.

Claims

1. An aluminosilicate molecular sieve of BOG framework type having a SiO2 / Al2O3 molar ratio of at least 10 and containing 1-adamantyl-3-propylimidazolium cations in its pores in its as-synthesized form.

2. The aluminosilicate molecular sieve of claim 1, wherein the SiO2 / Al2O3 molar ratio is in the range of 20 to 60.

3. The aluminosilicate molecular sieve of claim 1, wherein the framework is composed of TO4 tetrahedrons and the T atoms are silicon and aluminum atoms, and the framework structure contains less than 0.1% of framework impurities other than silicon and aluminum.

4. A method for synthesizing a BOG framework-type aluminosilicate molecular sieve, the method comprising: (1) preparing a reaction mixture, the reaction mixture comprising: (a) FAU framework zeolite; (b) an alkali metal or alkaline earth metal M source; (c) a structure directing agent comprising a 1-adamantyl-3-propylimidazolium cation Q; (d) a source of hydroxide ions; and (e) water; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the aluminosilicate molecular sieve; The reaction mixture has the following composition, in molar ratio: 。 5. The method of claim 4, wherein the reaction mixture has the following composition, in molar ratio: 。 The method of claim 4 , wherein the FAU framework-type zeolite is zeolite Y.

7. The method of claim 4, wherein the alkali metal or alkaline earth metal comprises sodium, potassium, or a combination thereof.

8. The process of claim 4, wherein the crystallization conditions comprise heating the reaction mixture at a temperature of 120°C to 200°C under autogenous pressure for a period of 1 day to 21 days.

Citation Information

Patent Citations

  • Catalyst that comprises at least one bog-structured zeolite and its use in transalkylation of alkyl-aromatic hydrocarbons

    US20050113618A1

  • Vehicle powertrain with on-board catalytic reformer

    US20200018268A1